The Semantics of Quiddity in Mir Damad's Metaphysics - Sayyed Muhammad Manafian (آموزه‌‌های فلسفه اسلامي, 2019)
The deliberate and explicit cognition of intention and the meaning of terms which have been applied by philosophers is one of the basic steps in cognizing theories and perceiving philosophical texts. It prevents to move towards the paralogism of homonyms. Mīr Dāmād is of the philosophers who has added new terms to the collection of Islamic philosophy terms from one side and from the other side, he has used some old and all-purpose terms in new meanings. Quiddity (måhiyyah) is one of these important terms in Mīr Dāmād's thought. It is impossible to be declared a true understanding and description of Mīr Dāmād's philosophical system without knowing the purpose of Mīr Dāmād in applying it. In the view of Mīr Dāmād, the meaning of quiddity is that by which something is what it is (må bihi huwa huwa). Therefore, quiddity is the criterion of the identity of a thing and everything in primary prediction (haml awwali) being applicable to a thing forms its own quiddity (måhiyyah).The position of the essence of mahiyyah is the level of hypothesis and presumption and when it has actual quiddity without any change and conversion, it leaves the hypothetical level and turns to real and fixation. The infinitive sense of wujud is taken solely from the level of reality of quiddity.